Residents’ perceptions of radon health risks: a qualitative study - Khan, Selim M; Chreim, Samia (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Radon is a high impact environmental pollutant and is the second leading cause of lung cancer in Canada. Building design, extended winter, and geographical location expose residents of Ottawa-Gatineau (the national capital region in Canada) to an increased risk. It is surprising that residents have an inadequate awareness of the risk - despite its gravity - and have taken minimum preventive actions. This study explores perceptions of radon health risk and examines the factors that enable and hinder the adoption of preventive measures among Ottawa-Gatineau residents. Methods We conducted semi-structured interviews with 35 residents with varying educational and income levels to inquire about their knowledge and perception of radon, and to explore their views of enablers and obstacles to taking action to reduce radon risks. Thematic, inductive data analysis was undertaken. Results The results indicate that: 1) Residents obtained information on radon from various sources that include the media, their education or occupation, their social network, and home renovation events. Limited references were made to the National Radon Program responsible for testing for radon and informing residents. 2) Awareness of radon risk varied, and the knowledge retained by some residents is insufficient to adequately protect their health. 3) Enablers for taking protective action included: having an understanding of the risk along with health consciousness; caring for family and children; knowing others who had contracted lung cancer and having financial resources. Obstacles consisted of: lack of awareness; cost; lack of home ownership; and potential difficulty in selling the house. 4) Residents attributed primary responsibility to public agencies for disseminating information, and incentivizing or mandating action through more stringent regulation. Conclusion Risk perceptions are subjective, and are influenced by micro and macro level factors. Inducing protective action to reduce risk requires comprehensive interventions taking into account the dual cognitive and emotional aspects of risk perception. Future research may explore the dual aspects of risk perception and examine the contents of the risk communication message. Policy should address the responsibility of both governments and residents in tackling the issue.